2007
DOI: 10.1002/env.837
|View full text |Cite
|
Sign up to set email alerts
|

Air quality monitoring using heterogeneous networks

Abstract: SUMMARYIn this paper, we consider some approaches to spatio-temporal modeling of environmental data obtained from an heterogeneous network.Besides discussing modeling details for spatio-temporal dynamics and calibration of different instruments, we consider crossvalidation issues and extensions to the monitoring network assessment based on sensitivity analysis.We then consider a case study based on the heterogeneous network related to fine particulate matter (PM 10 )coming from the Po Valley, North Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Such observations tend to agree with the findings of other studies conducted in the region on fine particulate (Cocchi et al 2006;Fassó et al 2007) and as such confirm that the area may be perceived, for both geographical, meteorological and anthropic reasons, as a part of a unique metropolitan area covering the entire Po Valley.…”
Section: Discussionsupporting
confidence: 81%
“…Such observations tend to agree with the findings of other studies conducted in the region on fine particulate (Cocchi et al 2006;Fassó et al 2007) and as such confirm that the area may be perceived, for both geographical, meteorological and anthropic reasons, as a part of a unique metropolitan area covering the entire Po Valley.…”
Section: Discussionsupporting
confidence: 81%
“…The methods, as presented in this paper, represent an alternative to a universal kriging-based approach, such as applied by Fassó et al (2007) (air quality) and Baume et al (2009) (radiation). The difference between the two approaches appears to be minor for estimation of biases for overlapping regions, something we also verified with simulations (results are not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Hence, there is an increased interest in merging the observations from local observation networks into larger databases. Some examples can be found in forestry (Köhl et al, 2000), soil quality (Wagner et al, 2001), air quality (Fassó et al, 2007) reported observations from Belgium might be systematically higher than the observations in the neighbouring countries. The Dutch network uses Bitt proportional counter RS03 with a self-effect of 2 nSv/h, whereas the Belgium network uses Berthold LB6360 with self-effect 11 nSv/h (Bossew et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…It was originally applied to predict air concentrations or to deal with error measurements in instruments (Fasso et al, 2007). This package uses the function Stem.Estimation to carry out the iterations of the EM algorithm until convergence.…”
Section: The State (S)-space Modelmentioning
confidence: 99%